2D Layered Double Hydroxide Nanosheets and Their Derivatives Toward Efficient Oxygen Evolution Reaction - Lu, Xueyi; Xue, Hairong; Gong, Hao; Bai, Mingjun; Tang, Daiming; Ma, Renzhi; Sasaki, Takayoshi (Nano-Micro Letters, 2020)
Layered double hydroxides (LDHs) have attracted tremendous research interest in widely spreading applications. Most notably, transition-metal-bearing LDHs are expected to serve as highly active electrocatalysts for oxygen evolution reaction (OER) due to their layered structure combined with versatile compositions. Furthermore, reducing the thickness of platelet LDH crystals to nanometer or even molecular scale via cleavage or delamination provides an important clue to enhance the activity. In this review, recent progresses on rational design of LDH nanosheets are reviewed, including direct synthesis via traditional coprecipitation, homogeneous precipitation, and newly developed topochemical oxidation as well as chemical exfoliation of parent LDH crystals. In addition, diverse strategies are introduced to modulate their electrochemical activity by tuning the composition of host metal cations and intercalated counter-anions, and incorporating dopants, cavities, and single atoms. In particular, hybridizing LDHs with conductive components or in situ growing them on conductive substrates to produce freestanding electrodes can further enhance their intrinsic catalytic activity. A brief discussion on future research directions and prospects is also summarized. Highlights: 1 Synthesis strategies of layered double hydroxides (LDHs) were summarized with classifications of traditional coprecipitation, homogeneous precipitation, and newly developed topochemical oxidation. 2 Diverse approaches of structural modulation and hybridization to enhance the electrocatalytic activity of LDHs were systematically reviewed.